Carotenoids gene markers for sweetpotato (Ipomoea batatas L. Lam): applications in genetic mapping, diversity evaluation and cross‑species transference - Arizio, Carla Marcela (2014)
Carotenoids play essential biological roles in plants, and genes involved in the carotenoid biosynthesis pathway are evolutionarily conserved. Orange sweetpotato is an important source of β-carotene, a precursor of vitamin A. In spite of this, only a few research studies have focussed on the molecular aspects of carotenoid genes regarding their specific sequence and structure. In this study, we used published carotenoid gene sequences from Ipomoea and other species for “exon-primed intron-crossing” approaches. Fifteen pairs of primers representing six carotenoid genes were designed for different introns, eleven of which amplified scorable and reproducible alleles. The sequence of PCR products showed high homology to the original ones. Moreover, the structure and sequence of the introns and exons from five carotenoid structural genes were partially defined. Intron length polymorphism and intron single nucleotide polymorphisms were detected in amplified sequences. Marker dosages and allelic segregations were analysed in a mapping population. The developed markers were evaluated in a set of Ipomoeas batatas accessions so as to analyse genetic diversity and conservation applicability. Using CG strategy combined with EPIC-PCR technique, we developed carotenoid gene markers in sweetpotato. We reported the first set of polymorphic Candidate Gene markers for I. batatas, and demonstrated transferability in seven wild Ipomoea species. We described the sequence and structure of carotenoid genes and introduced new information about genomic constitution and allele dosage.